2013
DOI: 10.1038/gim.2013.46
|View full text |Cite
|
Sign up to set email alerts
|

Insurance coverage of medical foods for treatment of inherited metabolic disorders

Abstract: Purpose Treatment of inherited metabolic disorders is accomplished by use of specialized diets employing medical foods and medically necessary supplements. Families seeking insurance coverage for these products express concern that coverage is often limited; the extent of this challenge is not well defined. Methods To learn about limitations in insurance coverage, parents of 305 children with inherited metabolic disorders completed a paper survey providing information about their use of medical foods, modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…A 2010 analysis by the Secretary's Advisory Committee on Heritable Disorders in Newborns and Children [17] and others in 2010 and 2013 [18, 19], showed that insurance coverage of medical foods and foods modified to be low in protein vary depending on the state of residence for the individual/family or type of their insurance plan. Thirty-two states were found to mandate some form of private insurance coverage if certain disorders were identified through NBS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2010 analysis by the Secretary's Advisory Committee on Heritable Disorders in Newborns and Children [17] and others in 2010 and 2013 [18, 19], showed that insurance coverage of medical foods and foods modified to be low in protein vary depending on the state of residence for the individual/family or type of their insurance plan. Thirty-two states were found to mandate some form of private insurance coverage if certain disorders were identified through NBS.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that 80% of children utilized at least two different types of nutritional products and almost half used three or more (e.g., a protein-containing medical food, plus foods modified to be low in protein, plus a dietary supplement) [19]. At the time of the survey, the costs of protein-containing medical foods were covered for most children through payment sources such as Medicaid, private insurance, and the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), while payment for foods modified to be low in protein were covered for only 40% of children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legislatures have utilized this tried and true approach in other preventive arenas, from mandated coverage for cancer screenings 142 to coverage for specialty medical foods and supplements recommended for individuals with inherited metabolic disorders tested for through state newborn screening programs, including phenylketonuria (PKU). 143 This approach would not prevent individuals from accessing, or clinicians and laboratories from offering, new genetic tests on the free market, but would ensure that once broad coverage for the predictive genetic test occurred, the interventions would be equitably reimbursed.…”
Section: Policy Mechanismsmentioning
confidence: 99%
“…1 In general, approximately 10.2 million children in the United States have special health care needs. 2 Despite the fact that many uninsured are now insured, current payment systems may impede coverage of medical foods.…”
mentioning
confidence: 99%